ЕТНОДЕМОГРАФІЧНІ ОСОБЛИВОСТІ РОЗВИТКУ СЕЛА ПІВДНЯ УКРАЇНИ У 60-80 рр. XX ст. (Zaporizhzhia Historical Review, 2021)
The ethnic picture of the countryside of the Southern part of Ukraine differed from the picture of the city and from the picture which was in the country regions of the Soviet Ukrainian Republic. Jhose southern districts were original which hadn’t been the subject of serious scientific generalization